The association between medical education accreditation and the examination performance of internationally educated physicians seeking certification in the United States - van Zanten, Marta (Perspect Med Educ, 2015)
The purpose of this study was to investigate the performance of graduates of international medical schools who seek Educational Commission for Foreign Medical Graduates certification based on accreditation of their medical education programmes. For the self-selected population who took United States Medical Licensing Examinations during the study period (2006–2010), accreditation was associated with higher first-attempt pass rates on some examinations, especially for international medical graduates from schools located in the Caribbean region. In addition, certain essential accreditation standards were associated with better performance on all examinations. This study lends support to the value of medical education accreditation.